2015
DOI: 10.1038/eye.2015.254
|View full text |Cite
|
Sign up to set email alerts
|

Spare the rods and spoil the retina: revisited

Abstract: Visual function improves with oxygen inhalation in people with diabetes even in the absence of visible retinopathy. Rods consume the most oxygen in the retina due to the high metabolic activity required to maintain the dark current. Therefore, Arden hypothesized that in diabetes where oxygen supply may also be affected due to the changes in retinal vasculature, prevention of dark adaptation may be a viable option to prevent or decrease the rate of progression of diabetic retinopathy. Animal experiments have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Several years ago, we reported that photoreceptor cells are the major site of that oxidative stress in the retina in diabetes [59], and experimental or genetic degeneration of those photoreceptors inhibited the diabetes-induced oxidative stress and upregulation of pro-inflammatory proteins. Consistent with the theories of Arden and colleagues [37,41,53], the presence or absence of light affects the retinal oxidative stress, resulting in the retinal oxidative stress caused by diabetes being worse in the dark [59]. Photoreceptors express NADPH oxidase [60] and contain most of the mitochondria found in the retina [61], and both of these can be sources of reactive oxygen species [59,62,63].…”
Section: How Might Photoreceptor Cells Contribute To Vascular Damage mentioning
confidence: 83%
“…Several years ago, we reported that photoreceptor cells are the major site of that oxidative stress in the retina in diabetes [59], and experimental or genetic degeneration of those photoreceptors inhibited the diabetes-induced oxidative stress and upregulation of pro-inflammatory proteins. Consistent with the theories of Arden and colleagues [37,41,53], the presence or absence of light affects the retinal oxidative stress, resulting in the retinal oxidative stress caused by diabetes being worse in the dark [59]. Photoreceptors express NADPH oxidase [60] and contain most of the mitochondria found in the retina [61], and both of these can be sources of reactive oxygen species [59,62,63].…”
Section: How Might Photoreceptor Cells Contribute To Vascular Damage mentioning
confidence: 83%
“…Interestingly, patients with RP and choroideremia rarely develop diabetic retinopathy (Arden ). As the rod activity is thought to be responsible for the presentation of diabetic retinopathy, in the absence of rods, the mitochondrial glycolysis would be reduced, and thus the production of oxygen‐free radicals (Sivaprasad & Arden ). It seems that retinal anoxia, which is a major pathogenetic factor in diabetic retinopathy, cannot develop in the presence of degenerative photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…63 In the avascular outer retina, rod photoreceptors are among the most metabolically active cells of the central nervous system and during darkness, the metabolic process requires the highest oxygen consumption of any tissue of the body. 65 The oxygen consumption of rods and cones increases as light levels fall. 65,66 OSA-induced hypoxia leads to inflammatory responses, vascular dysregulation, endothelial dysfunction, and oxidative damage, and it is thought to be one of the most critical pathogenesis factors for ischemic retinal diseases, such as proliferative diabetic retinopathy, retinal vessel occlusion, and oxygen-induced retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…65 The oxygen consumption of rods and cones increases as light levels fall. 65,66 OSA-induced hypoxia leads to inflammatory responses, vascular dysregulation, endothelial dysfunction, and oxidative damage, and it is thought to be one of the most critical pathogenesis factors for ischemic retinal diseases, such as proliferative diabetic retinopathy, retinal vessel occlusion, and oxygen-induced retinopathy. 5,6,15 Here, correlations between the PLR and sleep parameters indicated that a reduced peak pupil response to blue flash luminance at À2 and À1 log cd/m 2 (rod condition) was associated with reduced TST and increased levels of the ODI, respectively.…”
Section: Discussionmentioning
confidence: 99%